Exercise performance and thermoregulatory response to cold-water spray strategy: a scoping review - Salleh @ Othman, Farah Mat (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Introduction: In heat thermally stress conditions, fatigue occurs earlier and exercise capacity is reduced. In recent years, newer pre- and per-cooling devices have been developed but those devices seem logistically challenging for use in competition or field settings. Thus, this review aimed to analyse relevant literature of cold-water spray strategy effects on exercise performance and thermoregulatory response in a hot-humid environment. Methods: The search was conducted by applying the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines using ProQuest, ScienceDirect, PubMed, SpringerLink databases. Results: Eight publication studies were included. There were only three studies that investigated the effect of cold-water spray on exercise performance while five reported the cold-water spray intervention on thermoregulatory responses. Cold-water spray intervention improved exercise performance in three studies. Most of the studies showed that cooling by cold-water spray lower the forehead, face and skin temperatures, and heart rate while showing no significant effect on core body temperatures during exercise. Conclusion: Cooling intervention using cold-water spray could be an effective way of improving exercise performance in a hot environment. However, studies investigating the effectiveness of this cooling strategy are limited. Based on the current evidence, the effect of cold-water spray on core temperature shows no significant differences, while cardiovascular and skin temperature factors showed the opposite result.